Sectoral procurement within a capital group – selected issues (Discourse of Law and Administration, 2024)
Public utilities operating in the water, energy, transport and postal services sectors are obliged to apply public procurement rules to the appropriate extent. The application of this requirement is not linked in any way to the ownership structure of such a company, which means that it applies to public as well as private entrepreneurs. The author discusses sector contracts awarded within a functioning capital group, characterising what sector contracts are and in which situations the application of the Public Procurement Law is excluded. In the article, the author draws particular attention to the problems that sector procurers face when awarding contracts to entities belonging to the same capital group as the ordering party. The article contains a de lege ferenda proposal to introduce appropriate legal solutions aimed at minimising the occurrence of irregularities related to the application of the Public Procurement Law by sector procurers. In this respect, the author draws attention to the submission of declarations of interest or the use of the sole-source procurement procedure in the case of awarding contracts within a capital group.
Keywords: sectoral procurement; public procurement; capital group